Pembelajaran Kultur Jaringan Tanaman Obat Berbasis Project Base Learning (PjBL) Terintegrasi Lesson Study: Plant Tissue Culture Learning Based on Project Based Learning (PjBL) Integrated Lesson Study - Sapitri, Alfi; Tambunan, Muhammad Iqbal H.; Lubis, Retnita Ernayani; Arisetya, Dian (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
The learning process that occurs still focuses on the lecturer as the main source of knowledge. So, to develop superior graduate competencies, learning development is needed by implementing project based learning (PjBL) integrated lesson study in learning medicinal plant tissue culture. In project learning (PjBL) students are required to be able to master theoretical concepts in the field of knowledge in depth, procedurally, analyze data, be able to solve problems, make decisions based on information and data analysis, and provide and choose alternative solutions. The aim of this research is to increase the learning effectiveness of pharmacy students. The research method used is Development or Research and Development (R&D). Lesson Study activities are carried out in 3 stages, namely planning, implementing (do) accompanied by project-based learning, and reflection (see). The research subjects were 50 pharmacy students from Sari Mutiara University, Indonesia. The research results show that: the application of PjBL to medicinal plant tissue culture which is integrated in lesson study can improve student learning outcomes as seen from the pre-test results of 37.4% and post-test results of 83.9%. The project carried out by students on medicinal plant tissue culture in all 10 groups resulted in the production of 100% sterile media, the results of explant initiation were 94% sterile and the explants grew 99.3%.